The Influence of Product Quality and Price on Purchasing Decisions in Menumixfood MSMES in Cimahi City - Puspita Putri; Moh. Aep Nurjamad (International Journal of Scientific Multidisciplinary Research, 2024)
This study aims to analyze the effect of product quality and price on purchasing decisions at Menumixfood MSMEs in Cimahi City, West Java. The research method used is quantitative method with data collection techniques through questionnaires distributed to 203 respondents who are Menumixfood consumers. The data obtained was analyzed using multiple linear regression analysis. The results showed that product quality and price have a significant effect on purchasing decisions. Product quality has a more dominant influence than price. This study shows that improving product quality is more effective in influencing consumer purchasing decisions